PENERAPAN METODE SINGLE EXPONENTIAL SMOOTHING DALAM APLIKASI PERAMALAN PENCAIRAN KREDIT PADA PT. BPR MAGGA JAYA UTAMA - Tandika, Verga; Fenriana, Indah (ALGOR, 2023)
This research aims to apply the single exponential smoothing method in forecasting credit disbursement at PT. BPR Magga Jaya Utama. The single exponential smoothing method is a forecasting method that is suitable for forecasting time series data with a stable trend. Credit disbursement data at PT. BPR Magga Jaya Utama during the period January 2020 to December 2022 was used as research data. Data was analyzed using Microsoft Excel software. The research results show that the single exponential smoothing method can provide credit disbursement forecasting with a high level of accuracy. The resulting forecasting model can be used as a reference in making decisions regarding credit disbursement at PT. BPR Magga Jaya Utama. In this research, the best alpha value for the single exponential smoothing method was 0.3, with a Mean Absolute Percentage Error (MAPE) value of 3.94%. In conclusion, this research proves that the single exponential smoothing method can be applied in forecasting credit disbursement at PT. BPR Magga Jaya Utama. Accurate forecasting results can help PT. BPR Magga Jaya Utama in making better and more appropriate decisions regarding credit disbursement.